KESERASIAN SOSIAL DAN INTEGRASI SEBAGAI WUJUD KOMUNIKASI ANTAR ETNIK DIKELURAN PANASAKAN KECAMATAN BAOLAN KABUPATEN TOLITOLI - Ade Irma; Andi Famrizal; Fitriani Abdullah (Kinesik, 2023)
This study aims to determine social harmony and social integration as a form of inter-ethnic communication in Panasakan Village, Baolan Sub-district, Tolitoli Regency. The research base used is qualitative and the type of research is descriptive. The type of data uses primary data and secondary data. Data collection techniques are observation, interview, and documentation. Informant withdrawal technique using purposive. From the results of the research conducted, it is known that the process of inter-ethnic integration in Panasakan Village is formed through 4 (four) forms, namely marriage (amalgamation), work relationship attachment, community harmony institution (ethnic), community association (Rukun Warga/Rukun Tetangga). The four forms of integration above are a forum used by the people of Panasakan Village as a form of national integrity and as a supporting factor in creating social harmony in Panasakan Village, Baolan Sub-district, Tolitoli Regency, and the influence of communication as an inhibiting factor resulting in social conflict.